2021
DOI: 10.1016/j.isci.2021.103150
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guerin 's beneficial impact on glucose metabolism: Evidence for broad based applications

Abstract: Summary Bacillus Calmette-Guerin (BCG) vaccinations improve glycemic control in juvenile-onset Type I diabetes (T1D), an effect driven by restored sugar transport through aerobic glycolysis. In a pilot clinical trial, T1D, but not latent autoimmune diabetes of adults (LADA), exhibited lower blood sugars after multidose BCG. Using a glucose transport assay, monocytes from T1D subjects showed a large stimulation index with BCG exposures; LADA subjects showed minimal BCG-induced sugar responsiveness. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…Metformin inhibited the induction of altered immunity by BCG, as shown by a temporarily decreased induction of cytokine responses and lactate production upon secondary stimulation. We have also seen that metformin in vitro totally inhibits the normal BCG conversation of lymphoid cells from high oxidative phosphorylation to aerobic glycolysis [33]. This effect of metformin, now confirmed by two different research groups, may be the reason why reduced HbA1c in T2Ds are not observed post-BCG instillation for bladder cancer.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Metformin inhibited the induction of altered immunity by BCG, as shown by a temporarily decreased induction of cytokine responses and lactate production upon secondary stimulation. We have also seen that metformin in vitro totally inhibits the normal BCG conversation of lymphoid cells from high oxidative phosphorylation to aerobic glycolysis [33]. This effect of metformin, now confirmed by two different research groups, may be the reason why reduced HbA1c in T2Ds are not observed post-BCG instillation for bladder cancer.…”
Section: Discussionsupporting
confidence: 65%
“…The mechanism for improved HbA1c can be monitored by various complex or even simple methods such as sugar uptake in culture over set time periods with labeled sugar by registering fluorescence. For T2D, published data does not show an underlying defect in aerobic glycolysis suggesting a therapeutic effect of BCG may be less dramatic [33]. The capability of the lymphoid system being able to regulate blood glucose levels was hypothesized in 2007, where immune cells could transiently restrict the rise in blood glucose during and after a meal by buffering glucose in the form of lactate and aspartate [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptomic and metabolic data in our study revealed that BCG markedly enhanced glycolysis in newborn PMN-MDSCs. Several studies [9,[65][66][67][68] have shown that BCG can increase glycolytic metabolites in plasma or monocytes. Diray-Arce et al [65] measured that relative metabolite concentrations in neonatal plasma from a Boston in vitro cohort, and also identified glycolysis as one of the enriched pathways after BCG stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Diray-Arce et al [65] measured that relative metabolite concentrations in neonatal plasma from a Boston in vitro cohort, and also identified glycolysis as one of the enriched pathways after BCG stimulation. Shpilsky et al [66] found that monocytes from neonatal period BCG-vaccinated normal adult subjects continued to have accelerated glucose transport both at baseline and after in vitro BCG exposure compared with nonvaccinated control monocytes, implying that glucose uptake remains elevated decades after neonatal BCG vaccination. These findings are consistent with our observations in BCG-vaccinated neonatal mice.…”
Section: Discussionmentioning
confidence: 99%
“…The pertussis vaccine was divided into two parts, one was boiled and the other was left intact, and injected into STZ mice. T1D was not observed in mice treated with either regimen (132). It has been suggested to use Tregs to inhibit or remove pathogenic T cells in order to prevent or safeguard the function of b-cells.…”
Section: Bacteriamentioning
confidence: 99%